Analisis Implementasi Continuity of Care (COC) - Vita Raraningrum; Rizky Dwiyanti Yunita (Akademi Kesehatan Rustida, 2021)
This study aims to analyze the implementation of Continuity of Care (CoC) in the D.III Midwifery Study Program at the Rustida Health Academy, focusing on midwifery services through a model of continuous/sustainable service to women throughout pregnancy, childbirth, postpartum and family planning. Midwives as a subsystem of human resources become the spearhead that plays a direct role in accelerating the reduction in maternal or infant mortality. This research is a qualitative research, the research location is in the D.III Midwifery Study Program of Akes Rustida. The informants consist of CoC coordinator lecturers, Institutional Supervisors, land supervisors, students and clients. Data was collected through interviews, document review and participatory observation, with research indicators on continuous midwifery care for mothers and babies covering pregnancy, childbirth, newborns, postpartum and family planning. Data analysis used an interactive model. Research Results: Implementation of the CoC method in the final project report of the Rustida Health Academy students can demonstrate their competence to clients through the implementation of midwifery care. Clients are very satisfied with the assistance provided by students. The implementation of LTA using the CoC method has a positive impact on students, educational institutions as well as clients, while for students it can also provide real experience about midwifery care.